2018
DOI: 10.2147/ott.s183311
|View full text |Cite
|
Sign up to set email alerts
|

Quaternized chitosan promotes the antiproliferative effect of vemurafenib in melanoma cells by increasing cell permeability

Abstract: BackgroundAs one of the most invasive cutaneous carcinomas among all types of skin cancer, malignant melanoma remains a severe challenge in oncology and plastic surgery. Selective small-molecule inhibitors of V600E-mutant B-Raf (vemurafenib, for instance) have demonstrated satisfactory therapeutic efficacy in melanoma patients. However, acquired resistance during the period of drug administration has limited their clinical application.Materials and methodsIn the present study, human melanoma cells with the B-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Interestingly, polycationic QCh made electrostatic interactions with negatively charged cancerous cells that disturbed their cytoplasmic integrity. The investigation concluded that QCh upset the surface charges on melanoma cell, which may be an important parameter to change cell permeability [ 86 ]. Wongwanakul et al (2017) examined cell proliferation and cell differentiation properties of QCh on the intestinal barrier through CaCo-2 cell lines in vitro model.…”
Section: Biomedical Applications Of Quaternized Chitosan Derivativesmentioning
confidence: 99%
“…Interestingly, polycationic QCh made electrostatic interactions with negatively charged cancerous cells that disturbed their cytoplasmic integrity. The investigation concluded that QCh upset the surface charges on melanoma cell, which may be an important parameter to change cell permeability [ 86 ]. Wongwanakul et al (2017) examined cell proliferation and cell differentiation properties of QCh on the intestinal barrier through CaCo-2 cell lines in vitro model.…”
Section: Biomedical Applications Of Quaternized Chitosan Derivativesmentioning
confidence: 99%
“…Moreover, the effects of various specimens on cell apoptosis and cell cycle were determined using flow cytometry (BD LSRFortessa, BD Biosciences, Franklin Lakes, NJ, USA) as described in a previously reported method. 47 For cell apoptosis analysis, cells at a density of 5.0 × 10 5 per well were cocultured with the specimens for 48 h. Then, cells were collected after trypsinization and washed twice with phosphate buffer solution (PBS). Subsequently, cells were suspended in 500 μL of 1× binding buffer.…”
Section: Morphological and Chemical Characterizationsmentioning
confidence: 99%